Women and work: analyzing the mixed economy in Qikiqtarjuaq, Nunavut - Inksetter, Jocelyn B. (My University, 2012)
This thesis examines the condition of the mixed economy from the perspective of women's work in the Nunavut community of Qikiqtarjuaq. The focus of the project was to decide if the mixed economy persists in Inuit communities today, or if Inuit have moved into a new form of economy. I explored two definitions of the mixed economy. First, that as a group, women divide their time approximately evenly between monetary and subsistence pursuits; and second, that women devote their time to activities which support their male partners in hunting. A survey was used as the primary research tool to gather data from 103 women regarding how they spent their time over a one month period in spring 2010.
Keywords: Women & work; Mixed economy; Gender & work; Qikiqtarjuaq, Nunavut